Expression of the calcium-activated potassium channel in upper and lower segment human myometrium during pregnancy and parturition - Zhang Lanmei; Cong Binghai; Gao Lu; Ni Xin (BMC, 2009)
Abstract Background Large conductance calcium-activated potassium channel (BKCa) plays an important role in the control of uterine contractility during pregnancy. The change from uterine quiescence to enhanced contractile activity may be associated with the spatial and temporal expression of BKCa within myometrium. The objectives of this study were to examine the expression of BKCa alpha- and beta-subunit in upper segment (US) and lower segment (LS) regions of uterus, and to investigate for the possibly differential expression of these proteins in US and LS myometrium obtained from three functional states: (1) non-pregnant (NP); (2) term pregnant not in labour (TNL) and (3) term pregnant in labour (TL). Methods Myometrial biopsies were collected from non-pregnant women at hysterectomy and pregnant women at either elective caesarean section or emergency caesarean section. Protein expression level and cellular localization of BKCa alpha- and beta-subunit in US and LS myometrium were determined by Western blot analysis and immunohistochemistry, respectively. Results BKCa alpha- and beta-subunit were predominantly localized to myometrial smooth muscle in both US and LS myometrium obtained from non-pregnant and pregnant patients. The level of BKCa alpha-subunit in US but not in LS was significantly higher in NP myometrium than those measured in myometrium obtained during pregnancy. Lower expression of BKCa alpha-subunit in both US and LS was found in TL than in TNL biopsies. Expression of beta-subunit in both US and LS myometrium was significantly reduced in TL group compared with those measured in TNL group. There was no significant difference in BKCa beta-subunit expression in either US or LS between NP and TNL group. Conclusion Our results suggest that expression of BKCa alpha- and beta-subunit in pregnant myometrium is reduced during labour, which is consistent with the myometrial activity at the onset of parturition.